The Influence of Self-Esteem, Social Support, Parental Influence, Economic Consideration, and Personal Interest on Career Decision-Making among Generation Z Students - Syafiqo, Ebida Inas; Waskito, Jati (Journal of Economics and Social Sciences (JESS), 2025)
Career is one of the most important aspects, especially for fresh graduates. However, not all students are able to plan their careers well, and some struggle to map out their future paths. Therefore, this study examines the influence of self-esteem, social support, parental influence, economic considerations, and personal interests on career decision-making among Generation Z students. The sampling technique employed was purposive sampling, while data were collected through both primary and secondary methods. The analysis was conducted using SPSS. The findings reveal that the variables with the strongest influence on career decision-making (Y) are personal interest (X5) and self-esteem (X1). In contrast, social support (X2), parental influence (X3), and economic considerations (X4) do not have a significant impact on career decision-making (Y). Nevertheless, when considered simultaneously, all five independent variables exert a significant effect on the dependent variable. This study is expected to help fresh graduates plan their future more effectively by taking into account external factors that may shape their career choices.